How does food price increase affect Ugandan households?: An augmented multimarket approach - Ulimwengu, John M.; Ramadan, Racha (International Food Policy Research Institute, 2009)
Almost unaffected by the 2008 wave of soaring world food prices, Ugandan local market prices exhibit signs of high price volatility in the first quarter of 2009. At the household level, while net producers may reap some benefits from this increase in food prices, net consumers are more likely to suffer from it. However, the net consumption impact of food price increase is not as straightforward as reported in previous studies. In this paper, we extend Singh et al. (1986) multimarket model by adding demand elasticities from the Almost Ideal Demand System (AIDS). We use the integrated Ugandan National Household Survey (UNHS) 2005/2006 to estimate a measure of net consumption impact that includes both price and profit effects. Overall, we found that household welfare is expected to decrease with loss in consumption and increase with income gain as a result of higher food prices for the cereals producers. Simulating change in cereals consumption induced by a 50 percent increase in cereals price and taking into account the profit effect, our results predict a 23 percent decrease in food consumption for net sellers, compared with 44 percent when using the consumption approach alone. Accounting for such substitution effects, our results suggest that the impact of rising food prices may be mitigated because some households will attempt to substitute more expensive food items with cheaper ones; however, this apparent coping strategy often leads to a much poorer diet. The results suggest that the majority of households with expected positive income impact, the gainers, live in rural areas. These households also tend to have better access to agricultural services than the nongainers.